2005
DOI: 10.1111/j.1365-2141.2005.05477.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusion hybrids of dendritic cells and autologous myeloid blasts as a potential cellular vaccine for acute myeloid leukaemia

Abstract: SummaryWe assessed the potential of tumour cell/dendritic cell fusion hybrids to generate in vitro anti-leukaemic T-cell responses following co-culture with autologous remission lymphocytes in six patients with acute myeloid leukaemia (AML). Comparison was made to anti-leukaemic responses induced by mature dendritic cells (mDC) co-cultured with autologous, irradiated myeloid blasts. Fusion hybrids induced anti-leukaemic T-cell immune responses in three of six patients. Tumour-pulsed mDC induced T-cellular resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Several studies showed the induction of tumorspecific CTL in vitro by human DC/ tumor fusion cells. [16][17][18][19][20] Phase I/II clinical trials of DC/tumor cell fusion vaccines have been reported in patients with a range of tumors, including melanoma, renal and breast cancers, and multiple myeloma. [21][22][23][24][25][26][27][28][29] As is often the case, the results in clinical trials of DC/tumor fusion vaccines have been much less dramatic than in immunity (derived from the parent APC) (Fig.…”
Section: The Concept Of Apc/tumor Fusion Cell Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed the induction of tumorspecific CTL in vitro by human DC/ tumor fusion cells. [16][17][18][19][20] Phase I/II clinical trials of DC/tumor cell fusion vaccines have been reported in patients with a range of tumors, including melanoma, renal and breast cancers, and multiple myeloma. [21][22][23][24][25][26][27][28][29] As is often the case, the results in clinical trials of DC/tumor fusion vaccines have been much less dramatic than in immunity (derived from the parent APC) (Fig.…”
Section: The Concept Of Apc/tumor Fusion Cell Vaccinesmentioning
confidence: 99%
“…20,34 Adoptive CTL therapy has been used with clinical benefit in a range of tumor types, including hematological and nonhematological tumors. [37][38][39] Given some of the current uncertainties of APC/tumor cells as therapeutic cancer vaccines in humans, and the demonstrated ability of APC/tumor hybrid cells to induce tumor antigen-specific CTL in vitro, [16][17][18][19][20]34,35 themselves are short lived and have limited replicative capacity, limiting the numbers of fusion cells generated for use in vaccination. In addition, the nature of the processes of culture, isolation and cell fusion of DCs and ex vivo tumor cells limits standardization and characterization of the fusion cells.…”
Section: Potential Uses Of Hybrid Vaccines In Cancer Immunotherapymentioning
confidence: 99%
“…For example, pulsing of moDCs with apoptotic AML cells has a higher antigen-loading efficiency compared with pulsing with lysates (Galea-Lauri et al, 2002;van den Ancker et al, 2011). Fusion of DCs with AML cells also seems to be superior to loading with lysed or apoptotic leukemic cells (GaleaLauri et al, 2002;Klammer et al, 2005), although one report found no clear difference in functionality between lysate-pulsed DCs and AML-DC fusion hybrids (Weigel et al, 2006). The use of leukemiaderived exosomes and apoptotic blebs also seems to be superior to pulsing with lysates (Gu et al, 2015) and apoptotic tumor cells (Ruben et al, 2014), respectively.…”
Section: Reasonsmentioning
confidence: 99%
“…As outlined above, we have shown that LCL/tumour hybrid cell lines can induce tumour antigen-specific CTLs in PBMCs from both healthy individuals and tumour-bearing patients [27,66,67]. Given some of the current uncertainties of APC/tumour cells as therapeutic cancer vaccines in humans, and the demonstrated ability of APC/tumour hybrid cells to induce tumour antigen-specific CTL in vitro, [27,66,[72][73][74][75][76], the use of APC/tumour hybrid cells as inducers of tumour-specific CTLs for adoptive immunotherapy merits further investigation.…”
Section: Adoptive Immunotherapymentioning
confidence: 99%